Technika prawodawcza - Wronkowska, Sławomira (Digitalizacja i deponowanie archiwalnych zeszytów RPEiS sfinansowane przez MNiSW w ramach realizacji umowy nr 541/P-DUN/2016, 1990)
Legislative technique is nowadays of basic importance for securing the adequate level of legal systems. The article analyses the notion and tasks of legislative technique, characterizes the directives of legislative technique from a formal point of view (i.e. as sui generis technical direction), and from a substantive point of view, points to the deficiencies of contemporary legislative technique and analyses the problems of statutory regulation of legislative technique.
Legislative technique